DECISION SUPPORT SYSTEM FOR FOOD MENU SELECTION FOR PATIENTS WITH TYPHOID FEVER USING THE TOPSIS METHOD - Akhmad Aris Tantowi; Didik Wiguna (Yayasan Nuraini Ibrahim Mandiri, 2025)
A decision support system (DSS) is a system that can help users find the best solution. The decision support system (DSS) has several implementation methods. One of the Decision Support System (DSS) methods is the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS). The TOPSIS method is a weighted summation method with specified criteria. In this study, it was conducted to recommend the best food for typhoid patients. The results of the study found that the requirements determined for the best food recommendations were the nutritional content and condition of the patient. The nutritional content of food such as protein, carbohydrates, fat, fiber, vitamins, and minerals. The patient's condition consists of age, test results, weight, patient symptoms, and severity. Implementation of the Decision Support System (DSS) with the TOPSIS method in a case study in the form of a web application using the PHP programming language. The application makes it easy to recommend the best food for typhoid patients according to the patient's condition criteria. In addition, the flexibility of the application can provide convenience to add a list of foods along with the nutritional content of the food.